Failed repair of isolated female epispadias: Insights and outcome of single stage repair - Abdul Rouf Khawaja; Farzana Bashir; Javaid Magray; Ashiq hussain; Sajad Malik; Arif Hamid; Mohd Saleem Wani (Archive of Urological Research - Peertechz Publications, 2020)
Female epispadias without exstrophy is a very rare entity and occurs one in 480,000 female population. Early surgical reconstruction of the bladder neck,urethra and external genitalia is important in establishing urinary continence and to reduce psychological stress on the parents and child.In this case report we present a 25 year unmarried female presented with failure to achieve continence after bladder neck reconstruction at age 4year by urologist. Due to previous surgical failure, Patient developed psychological problems with poor esteem and wants a procedure which makes her life socially acceptable. A continent cutaneous urinary diversion was done at a single procedure with a follow up of 02 year. Patient is continent with pouch capacity about 400ml and emptying her pouch every 4hrly and actively involving in social activities, enjoying an excellent lifestyle, accepted body image and good personal satisfaction.